Penerapan Sisa Material Kayu dan Triplek Sebagai Elemen Kedap Suara Dalam Bangunan - Jati, Yosafat Danang Kukuh Bismo; Soli, Januarius Basilius Agung; Putra, Heristama Anugerah (Jurnal Lingkungan Karya Arsitektur, 2024)
Waste material is a very serious problem in the world of building construction. Efforts to reduce the use of new materials and reuse leftover materials can have a positive impact on the environment. Moreover, many building materials cannot be renewed so they are only used once. Apart from that, producing new materials requires the use of quite a lot of energy. There are many new materials, but this does not rule out the possibility that wood-based materials are still widely used. Wood is a type of building material that has a natural grooved character and is able to withstand noise and weather. The aim of this research is to determine the difference in soundproofing between wood and plywood materials in semi-permanent buildings. The method used was an experimental trial using the CoolExp software cellphone application to measure the decibel sound from each experiment. This research data was obtained through several experiments from several types of sounds, namely, knocking sounds, the sound of pebbles being dropped, the sound of music, the sound of people talking, the sound of vehicles. The results of the research show that: (1) the sound of knocking on wooden material is more soundproof (2) the sound of pebbles being dropped on wooden material is more soundproof (3) the sound of music on wooden material is more soundproof (4) the sound of people talking on tripek material is more soundproof (5) the sound of plywood material vehicles is more soundproof.